Proceedings of the 2014 IEEE Emerging Technology and Factory Automation (ETFA) 2014
DOI: 10.1109/etfa.2014.7005088
|View full text |Cite
|
Sign up to set email alerts
|

IEC 61499 based model-driven process control engineering

Abstract: In process control engineering, most requirements for the control system are conventionally specified in piping and instrumentation diagrams (P&IDs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Some studies specific to the process control engineering domain also covered the early design of control systems, for example, the approaches proposed by Hästbacka et al 10 and Pang et al 35 In their works, requirements are modelled according to the P&ID IEC 62424 standard; 36 then, corresponding component networks which realize the requirements are automatically generated via model transformations. Considering the specificity of this domain, these approaches cannot be applied to the distributed manufacturing system development.…”
Section: Related Workmentioning
confidence: 99%
“…Some studies specific to the process control engineering domain also covered the early design of control systems, for example, the approaches proposed by Hästbacka et al 10 and Pang et al 35 In their works, requirements are modelled according to the P&ID IEC 62424 standard; 36 then, corresponding component networks which realize the requirements are automatically generated via model transformations. Considering the specificity of this domain, these approaches cannot be applied to the distributed manufacturing system development.…”
Section: Related Workmentioning
confidence: 99%
“…IV. USE CASE: ORCHESTRATION FROM PROCESS & INSTRUMENTATION DIAGRAM Pang et al [26] have shown how a system described by an IEC 62424 Process and Instrumentation Diagram (P&ID) can be formally transformed to IEC 61499 applications. Using part of the P&ID in their example to create a Plant Description, it can then be used to illustrate how orchestration rules might be generated for a System-of-System, based on service interactions.…”
Section: B Orchestration Of Systemsmentioning
confidence: 99%
“…For the area of software engineering in industrial automation Vyatkin [7] presents an overview of the current solutions and concepts, where the role of standards such as IEC 61499 [8] and IEC 61850 [9] are highlighted, and the use of modeldriven software engineering in automation is presented as one of the compelling paths for further development in the area. One example of model-driven software engineering that uses structured standards would be the method presented by Pang et al [10] for how the Piping and Instrumentation Diagrams (P&ID's) following the standard IEC 62424 [11] can be translated into IEC 61499 Function Blocks (FB's) commonly used in programming automation systems for the process industry.…”
Section: Introductionmentioning
confidence: 99%